A Study of Quality Assurance Practices in the Universiti Sains Malaysia (USM), Malaysia - Khoo, Helen Chooi Sim; Idrus, Rozhan M. (Anadolu University, 2001)
This article looks at the quality assurance practices amongst three (3) groups of staff in the School of Distance Education, Universiti Sains Malaysia, i.e. lecturers, resident tutors and support staff. 9 dimensions of the Quality Assurance Practices i.e. Staff Development, Planning, Work Process, Team Work, Prioritise Customers, Performance Evaluation, System For Sending Of Learning Materials, System For Receiving Of Assignments From Students and Management of Students’ Records are identified in this study. The results show that quality assurances practices amongst three groups are different. Profile Analysis used in this research shows that quality assurance practices amongst lecturers and support staff are parallel. Results also show that quality assurance practices of resident tutors have profiles that differ from the lecturers and support staff.